2017
DOI: 10.1161/jaha.116.004739
|View full text |Cite
|
Sign up to set email alerts
|

Local Ancestry and Clinical Cardiovascular Events Among African Americans From the Atherosclerosis Risk in Communities Study

Abstract: BackgroundLocal ancestry in relation to clinical cardiovascular events (CVEs) among African Americans can provide insight into their genetic susceptibility to the disease.Methods and ResultsWe examined local European ancestry (LEA) association with CVEs among 3000 African Americans from the Atherosclerosis Risk in Communities Study (ARIC). We estimated LEA using Local Ancestry Inference in adMixed Populations using Linkage Disequilibrium (LAMP‐LD) and examined its association with myocardial infarction, stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 51 publications
3
19
0
1
Order By: Relevance
“…The Lin52 (protein Lin52) which was significantly up-regulated in SHS has been associated with clinical CV events among African Americans from atherosclerosis risk communities' study. A genome-wide analysis of meta-analysis study by Shendre et al (2017) showed the presence of Lin52 gene in African-American of CV events such as stroke, atherosclerosis and myocardial infarction incidents. However, the study did not further evaluate the functional role of this gene with the occurring of these diseases and suggested further studies.…”
Section: Subfornical Organ (Sfo)mentioning
confidence: 99%
“…The Lin52 (protein Lin52) which was significantly up-regulated in SHS has been associated with clinical CV events among African Americans from atherosclerosis risk communities' study. A genome-wide analysis of meta-analysis study by Shendre et al (2017) showed the presence of Lin52 gene in African-American of CV events such as stroke, atherosclerosis and myocardial infarction incidents. However, the study did not further evaluate the functional role of this gene with the occurring of these diseases and suggested further studies.…”
Section: Subfornical Organ (Sfo)mentioning
confidence: 99%
“…Moreover, smooth muscle cell–specific inducible knockout of sGC β in mice results in hypertension, suggesting sGC expression in smooth muscle cells is critical for modulating vascular tone ( Groneberg et al, 2010 ). Genome-wide association studies of single nucleotide polymorphisms also identified genetic variants within the sGC genes GUCY1A3 and GUCY1B3 as being associated with a high risk for cardiovascular disease ( Ehret et al, 2011 ; Wobst et al, 2015 ; Shendre et al, 2017 ). Of translational importance, small-molecule sGC modulators have been developed for clinical use to restore disease-associated loss of sGC activity and cGMP production to varying degrees of success ( Yoshina et al, 1978 ; Stasch et al, 2001 ; Frey et al, 2008 ; Meurer et al, 2009 ; Mittendorf et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is a major public health concern, leading to tremendous health and economic burdens globally [1]. The pathogenesis of stroke is highly complex, and both genetic and environmental factors could increase stroke predisposition in humans [2]. Arterial endothelial dysfunction and atherosclerosis have been listed as important risk factors for stroke [3].…”
Section: Introductionmentioning
confidence: 99%